Avaliação do papel da glutamina nos desfechos relacionados ao transplante alogênico de células-tronco hematopoiéticas - Henrique Oswaldo da Gama Torres (2008)
Fifty-three patients with hematological malignancies who underwent allogeneic stem cell transplantation (SCT) from HLA-identical siblings were randomly assigned to receive glutamine enriched parenteral nutrition - PN (GlPN, n = 27) or standard PN (PN, n = 26), inisonitrogenous solutions. Deaths (D+100 and D+180), infections, acute GVHD, length of stay (LOS), time of neutropenia and intestinal permeability (IP) were studied. Ages, gender, diagnosis, disease status and treatment variables were equally distributed between groups. Survival on D+180 was increased in GlPN (74%) vs. PN (46 %), p= 0.03(log-rank), reaching the limit of statistical significance on D+100 (p = 0.05). Most deaths occurred before D+100, especially in PN (10/26, 39 %) versus 15 % (4/27) in GlPN. GVHD was the most frequent cause of death (8/21, 38%), especially in PN (n = 6, 5 before D+100). Other outcomes were not affected. IP was affected on admission, was not affected by glutamine enrichment, but consistently worsened throughout the study. Results showed that glutamine enriched PN was efficacious in increasing short-term survival after allo-SCT. Benefits of glutamine seem to be independent of mucosal protection, as IP was not affected by its use. A trend to a lower incidence of GVHD deaths may suggest animmunomodulatory role of glutamine.